Caracterización epidemiológica y clínica de pacientes operados con diagnóstico de quiste branquial - Aguirre R., Noemí; Bravo C., Gustavo; Araneda R., Felipe; Celedon L., Carlos; Gac E., Patricio; Cabané T., Patricio (Revista Hospital Clínico Universidad de Chile, 2013)
Introduction: Branchial Cysts are uncommon anomalies in regular clinical practice. However, among congenital cervical cysts, they represent about 30% from total. Objective: Characterize patients diagnosed with operated branquial cyst in our clinical center, and correlate clinic, imaging and final diagnose. Material and methods: Retrospective descriptive study of discharged patients diagnosed as cervical cysts, between January 2005 and July 2011, at Hospital Clinico Universidad de Chile. Selection of Clinical records with final diagnose of branchial cyst were selected. Age, sex, clinical story, imaging exams, pre-operative and post-operative diagnoses, and biopsy report were registered. Results: from a total of 149 cervical cysts, 31 (20,8%) were branchial cysts. Man 45% and women 55%. By age, 9 (29%) were < 15 years old (average: 6,69 years) and 22 (70,9%) > 15 years (average: 33,7 years). Lateral cervical mass was the most common clinical manifestation. Regarding Imaging study, 15 cervical ultrasounds (sensibility 0,86 and specificity 0,98) and 13 cervical CTA scans (sensibility 0,92 and specificity 0,94) were conducted. In 9 patients, imaging studies weren’t conducted for the clinical diagnose (sensibility 0,77 and specificity 0,98). Correlation of pre-operative and post-operative diagnose was 87%. Discussion: According to literature, presentation age is generally during childhood; however, in our statistics it presented during adult age, which could be explained due to the main focus our medical center has for adult population. Most common clinical presentation was lateral neck mass, which had a good clinical correlation, however improves with imaging studies.